Implementasi Framework Laravel Pada Aplikasi Godebook Berbasis Website Dengan Metode Extreme Programming Di Gify Tech - Apriwinda Rahmayani; Mochamad Adhari Adiguna (JUPIK : Jurnal Penelitian Ilmu komputer, 2024)
This research discusses the implementation of the Laravel framework in developing web-based GodeBook applications using the Extreme Programming (XP) method at Gify Tech. GodeBook is an application designed to provide a platform for users to access and share e-books. The XP method is used to ensure software development that is adaptive and responsive to changing user needs. This research covers the stages of application development, from planning to testing, with the application of XP principles such as intensive communication, continuous testing, and incremental development. The Laravel framework was chosen because of its advantages in simplifying the web development process, providing an organized structure, and supporting good development practices. The results of this implementation are expected to increase development efficiency, quality and reliability of the GodeBook application. By using XP and Laravel, it is hoped that we can overcome software development challenges in a more collaborative, responsive and adaptive way.   Keywords: Laravel Framework, GodeBook Application, Extreme Programming (XP) Method, Collaborative, Responsive, Adaptive, Efficient.